Hakikat Ilmu Pengetahuan dan Pencarinya: Sebuah Ikhtiar untuk Mendasari Kajian Multidisipliner - Asmuki Asmuki (LP2M Universitas Ibrahimy, 2023)
The limited human absorption capacity necessitates the incompleteness of the captured object. In turn, the knowledge possessed by humans is incomplete. Then came the phenomenon of dichotomy of science, such as religion and general. This dichotomy is widening along with the demand for specific specifications and specializations for certain problems. Many people misunderstand this phenomenon that the nature of knowledge is dichotomous and the seekers are limited by the classroom and study period. This library research was carried out by collecting literature on knowledge and its seekers from authoritative literature such as interpretations, hadiths, turats books, and so on. The findings that can be conveyed are that the nature of knowledge is one-solid, and to obtain it is not limited to space and time. This article also provides a philosophical basis for publishing this Jurnal Multidisiplin Ibrahimy (JUMMY).